Participation of KKN Students in Teaching PAI at MA DDI Ar-Rahman Jawi-Jawi, Bone Village, Segeri District, Pangkajene Regency and Islands - Sirajuddin, Sirajuddin; Habib, Nur Muhammad (Journal of English Language and Education, 2024)
This study aims to analyze the contribution of KKN students in teaching Islamic Religious Education in Bone Village, Segeri District, Pangkep Regency, South Sulawesi. This KKN program generally aims to provide direct experience to students in applying science in the community and improving the quality of learning at Madrasah Aliyah (MA) DDI Ar-Rahman Jawi-Jawi and DDI Jawi-Jawi Junior High School. In particular, this research focuses on efforts to improve students' understanding of Islam, as well as help students understand the subject matter in a more in-depth and fun way. The method of implementing KKN includes socialization with village officials, surveys and data collection of schools and students, coordination with Islamic Religious Education (PAI) teachers for material adjustments, as well as various learning methods, such as questions and answers, quizzes, educational games, and interesting visual media. In addition, students also use demonstration and simulation methods for worship practices such as ablution, prayer, azan, tayamum, and storytelling by telling the stories of the prophet and companions. Learning-based projects are also carried out by asking students to create simple projects such as da'wah posters or lecture videos. The results of the study show that the KKN program has succeeded in improving students' understanding of Islam, the quality of learning, and helping the teaching and learning process. In addition, this program provides real experience to students in applying science and strengthening social ties between students and society. This research contributes to developing an effective teaching model that can be applied in other villages with similar conditions.